Spectral-Based Fatigue Life Analysis of Bus Structural Steels with Different Nodes and Operating Tracks - DEWA, Rando Tungga; EKAPUTRA, I. Made Wicaksana; KEPKA, Miloslav; ADINATA, Daffa Mandala (Engineering Transactions, 2023)
This paper shows a study on the effect of different structure nodes and operating tracks on the loaded/emptied type of bus vehicle in the Czech Republic. Five different structural nodes are selected to represent the loading capacity of the bus. City track and testing ground data measurements are performed for comparison. Accelerated durability test for fatigue life assessment can be performed on the testing ground with determined test track composition. The results are expected to show different characteristics of stress spectra influencing the structure’s fatigue life. The fatigue life calculation is performed based on deterministic procedures for a structural component. The procedure is then statistically expanded to include mathematical extrapolation on the stress spectra for all measurements of the designed life.